Is there a different impact of traditional risk factors on calcium score, in an asymptomatic population?. (14th October 2021) - Temtem, M; Serrao, M; Mendonca, M I; Santos, M; Sousa, J A; Mendonca, F; Sousa, A C; Freitas, S; Henriques, E; Rodrigues, M; Borges, S; Guerra, G; et al.
Abstract: Background: The coronary calcium score has been increasingly used to stratify and predict cardiovascular risk, particularly in low and intermediate-risk persons. Understanding which determinants have more impact on coronary calcium score level, could lead to the development of new stricter preventive measures for reducing coronary artery calcification (CAC) and, consequently, cardiovascular risk. Purpose: Our study aimed to investigate the impact of the traditional risk factors (TRFs) on the CAC score level and if there is a different association between this TRFs and CAC score degrees, in an asymptomatic population. Methods: The study cohort comprised 1, 122 consecutive asymptomatic individuals without known coronary artery disease (CAD) belonging to the healthy controls of GENEMACOR study and referred for computed tomography for CAC scoring assessment. The traditional risk factors considered were (1) current cigarette smoking, (2) dyslipidemia, (3) diabetes mellitus, (4) hypertension and (5) family history of coronary artery disease. According to the Hoff's nomogram, 3 categories were created: low CAC (0≤CAC<100 and P<50); moderate CAC (100≤CAC<400 or P50–75) and high or severe CAC (CAC≥400 or P>75). We evaluated the association of the different TRFs with these levels of CAC score (Chi-square test). Finally, we performed a logistic regression model adjusted for all significant TRFs selected in the bivariate analyses. Results: Smoking was significantly associated with high levels of CAC score, 28.4% vs 21.7%; p=0.038 as well as hypertension, 58.8% vs 45.6%; p=0.001, type 2 diabetes 21.1% vs 9.6%; p<0.0001, dyslipidemia, 73.0% vs 66.1%; p=0.057. Family history did not show a significant association with CAC (p=0.717). Then, we constructed a logistic regression model adjusted the significant risk factors in previous analysis. The final multivariate analysis, selected as independent predictors of high CAC: Type 2 diabetes; OR=2.309; 95% CI 1.533–3.479; p<0.0001, hypertension; OR=1.627; 95% CI 1.185–2.233; p=0.003, and smoking, OR=1.565; 95% CI 1.102–2.222; p=0.012. Conclusions: In this study, well-known and modifiable cardiovascular risk factors are associated with high calcium score levels. However, hypertension and diabetes seem to be preferentially associated with higher CAC scores, while tobacco, although it has a significant association, seems to be not so strong as diabetes and hypertension. This concept may mean that smoking has its primary role in plaque instability and not so much in the growing and calcification of plaques. Funding Acknowledgement: Type of funding sources: None.